2004
DOI: 10.2337/diabetes.53.1.179
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vessel Diameters and the Incidence of Gross Proteinuria and Renal Insufficiency in People With Type 1 Diabetes

Abstract: Early retinal vessel caliber changes may predict risk of diabetic nephropathy. We examined the association of retinal vessel diameters and the incidence of gross proteinuria and renal insufficiency in a populationbased cohort of people with type 1 diabetes (n ‫؍‬ 557). Baseline retinal photographs were digitized, and diameters of individual retinal vessels were measured and summarized. Incident cases of gross proteinuria and renal insufficiency were identified over a 16-year period. Larger retinal venular diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
88
3
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 36 publications
5
88
3
2
Order By: Relevance
“…Both cross-sectional and prospective data from the Wisconsin Epidemiological Study of Diabetic Retinopathy (WESDR) [10,34] show that wider venular calibre is associated with severity and progression of retinopathy and with other microvascular complications, such as gross proteinuria and nephropathy [11]. However, despite the consistency of our study findings with the WESDR, the biological mechanisms that underlie these associations are uncertain, and may reflect increased retinal blood flow secondary to a combination of hyper-glycaemia [35] retinal hypoxia [9,36], inflammation [37], increased lactate production [38] and/or endothelial dysfunction [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both cross-sectional and prospective data from the Wisconsin Epidemiological Study of Diabetic Retinopathy (WESDR) [10,34] show that wider venular calibre is associated with severity and progression of retinopathy and with other microvascular complications, such as gross proteinuria and nephropathy [11]. However, despite the consistency of our study findings with the WESDR, the biological mechanisms that underlie these associations are uncertain, and may reflect increased retinal blood flow secondary to a combination of hyper-glycaemia [35] retinal hypoxia [9,36], inflammation [37], increased lactate production [38] and/or endothelial dysfunction [39].…”
Section: Discussionmentioning
confidence: 99%
“…Using these new methods, several studies have shown that changes in retinal vascular calibre are associated with the risk of developing type 2 diabetes [7,8] and impaired fasting glucose (IFG) [9] and, among people with diabetes, with progression of retinopathy [10] and nephropathy [11]. However, there is a significant gap in the current literature concerning a clear understanding of how retinal vascular calibre changes with increasing severity of glucose intolerance [12].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence to date suggests that wider retinal venular diameters are associated with presence of both DN and severe levels of DR in several cross-sectional studies (3,(8)(9)(10) and with incident DN (4,5) and progression to severe DR (13,14) in prospective studies. No relations between retinal venular diameters and DPN have been shown thus far (2,4,6,7).…”
mentioning
confidence: 98%
“…Studies have investigated how retinal vessel calibers are associated with microvascular complications in both type 1 and type 2 diabetes (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The evidence to date suggests that wider retinal venular diameters are associated with presence of both DN and severe levels of DR in several cross-sectional studies (3,(8)(9)(10) and with incident DN (4,5) and progression to severe DR (13,14) in prospective studies.…”
mentioning
confidence: 99%
“…Measurements of vessel calibres in retinal photos could potentially deliver such biomarkers [3][4][5][6][7], but more global variables are available, for example retinal vascular fractal dimensions. The fractal dimension summarises the complexity and density of branching structures characterised by selfsimilarity and a similar level of complexity despite changes in magnification (for example snowflakes, tree branches, lightning).…”
Section: Introductionmentioning
confidence: 99%